Managing Social Change: A Figural or Process Sociological Approach to Understanding Organizational Management within the NHS - Dopson, S; Waddington, I (1996)
Using the implementation of the Griffiths Report as an example, this paper examines the way in which sociologists and others have examined the process of managing change within the NHS. Several studies of Griffiths have documented a number of unintended consequences of its implementation but it is argued that none of these have adequately theorised these unintended outcomes of the policy implementation process. It is suggested that the process-sociological approach of Norbert Elias, and in particular his game models, enable us better to understand the complex interweaving of planned and unplanned processes which is involved in all processes of managed change.